Complement-regulatory biomaterial coatings: Activity and selectivity profile of the factor H-binding peptide 5C6. (1st January 2023) - Bechtler, Clément; Koutsogiannaki, Sophia; Umnyakova, Ekaterina; Hamid, Amal; Gautam, Avneesh; Sarigiannis, Yiannis; Pouw, Richard B.; Lamers, Christina; Rabbani, Said; Schmidt, Christoph Q.; Lambris, John D.; Ricklin, Daniel
Abstract: The use of biomaterials in modern medicine has enabled advanced drug delivery strategies and led to reduced morbidity and mortality in a variety of interventions such as transplantation or hemodialysis. However, immune-mediated reactions still present a serious complication of these applications. One of the drivers of such reactions is the complement system, a central part of humoral innate immunity that acts as a first-in-line defense system in its own right but also coordinates other host defense responses. A major regulator of the complement system is the abundant plasma protein factor H (FH), which impairs the amplification of complement responses. Previously, we could show that it is possible to recruit FH to biomedical surfaces using the phage display-derived cyclic peptide 5C6 and, consequently, reduce deposition of C3b, an activation product of the complement system. However, the optimal orientation of 5C6 on surfaces, structural determinants within the peptide for the binding, and the exact binding region on FH remained unknown. Here, we show that the cyclic core and C-terminal region of 5C6 are essential for its interaction with FH and that coating through its N-terminus strongly increases FH recruitment and reduces C3-mediated opsonization in a microparticle-based assay. Furthermore, we could demonstrate that 5C6 selectively binds to FH but not to related proteins. The observation that 5C6 also binds murine FH raises the potential for translational evaluation in animal models. This work provides important insight for the future development of 5C6 as a probe or therapeutic entity to reduce complement activation on biomaterials. Statement of significance: Biomaterials have evolved into core technologies critical to biomedical and drug delivery applications alike, yet their safe and efficient use may be adversely impacted by immune responses to the foreign materials. Taking inspiration from microbial immune evasion strategies, our group developed a peptide-based surface coating that recruits factor H (FH), a host regulator of the complement system, from plasma to the material surface and prevents unwanted activation of this innate immunity pathway. In this study, we identified the molecular determinants that define the interaction between FH and the coated peptide, developed tethering strategies with largely enhanced binding capacity and provided important insight into the target selectivity and species specificity of the FH-binding peptide, thereby paving the way for preclinical development steps. Graphical abstract: Image, graphical abstract